2005
DOI: 10.1108/01437730510617645
|View full text |Cite
|
Sign up to set email alerts
|

Organizational socialization, career aspirations and turnover intentions among design engineers

Abstract: Purpose -Turnover intention is one's behavioural intention to quit. The purpose of this study is to compare the relative influences of organizational socialization and career aspirations on turnover intentions of design engineers and to address the design of more effective development programmes and the reduction of dysfunctional turnover. Design/methodology/approach -A study of 442 engineers staffed within "design and development" units is presented, and a research model is tested using structural equation mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
85
1
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(92 citation statements)
references
References 31 publications
0
85
1
6
Order By: Relevance
“…The employees with lower satisfaction levels on identity, job security, and technical advancement often have a lower level of career satisfaction and a higher rate of turnover (Herzberg et al, 1959). Bigliardi et al (2005) believed that the extent of one's "internal career anchors" should be viewed as an individual's career motivations and they assert that external opportunities provided by an organization was negatively associated with turnover intentions.…”
Section: Research Hypothesis Developmentmentioning
confidence: 99%
See 3 more Smart Citations
“…The employees with lower satisfaction levels on identity, job security, and technical advancement often have a lower level of career satisfaction and a higher rate of turnover (Herzberg et al, 1959). Bigliardi et al (2005) believed that the extent of one's "internal career anchors" should be viewed as an individual's career motivations and they assert that external opportunities provided by an organization was negatively associated with turnover intentions.…”
Section: Research Hypothesis Developmentmentioning
confidence: 99%
“…Based on the results, it is indicated that role ambiguity and role conflict influenced job performance. Taormina (1997), fits all these dimensions into four generalized constructs that are used by Bigliardi et al (2005) and in the present study:…”
Section: Organizational Socializationmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies such as Cohen and Golan (2007) and Park and Kim (2009) have investigated the relationship between intent to quit and job satisfaction, while Bigliardi, Petroni and Dormio (2005) linked intent to quit to interpersonal relationship. However, none of these studies have specifically focused on the commitment and intent to leave of IT engineers in relation to their managers' traits.…”
Section: Onimentioning
confidence: 99%